2018
DOI: 10.2147/oajsm.s160306
|View full text |Cite
|
Sign up to set email alerts
|

Australian cardiac rehabilitation exercise parameter characteristics and perceptions of high-intensity interval training: a cross-sectional survey

Abstract: PurposeThis study explored current demographics, characteristics, costs, evaluation methods, and outcome measures used in Australian cardiac rehabilitation (CR) programs. It also determined the actual usage and perceptions of high-intensity interval training (HIIT).MethodsA cross-sectional observational web-based survey was distributed to 328 Australian CR programs nationally.ResultsA total of 261 programs completed the survey (79.6% response rate). Most Australian CR programs were located in a hospital settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…No cardiac events reported were related to exercise training, which suggests that exercise and the addition of WPAM does not increase incidences of cardiac events. This is in line with numerous studies that have shown low adverse event rates with CR exercise [23, 77, 78]. The specific effect of WPAM on safety cannot be determined from these studies, as only one reported which group (control or intervention) the participants who suffered an adverse event were in.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…No cardiac events reported were related to exercise training, which suggests that exercise and the addition of WPAM does not increase incidences of cardiac events. This is in line with numerous studies that have shown low adverse event rates with CR exercise [23, 77, 78]. The specific effect of WPAM on safety cannot be determined from these studies, as only one reported which group (control or intervention) the participants who suffered an adverse event were in.…”
Section: Discussionsupporting
confidence: 79%
“…Several countries have reported one fifth to one third of eligible patients enrol in CR [1922]. Australia has reported a higher enrolment rate (51–80%) [23]. To improve this low uptake, researchers have investigated alternate models of CR delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies from the United Kingdom have highlighted that in CR practice the actual exercise training intensities performed by patients, may not progress to the upper range of exercise intensity recommendations (13). Despite numerous publications outlining international CR practices and program characteristics from national registries or surveys, relatively few include data on exercise intensity prescription or implementation (15)(16)(17)(18). This data is important to determine whether exercise training during CR is being prescribed and implemented effectively across international programs.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings share some consistency with results from previous Australian surveys. Specifically, the majority of survey responses were from New South Wales and Victoria, 13 exercise was commonly supervised by a nurse or physiotherapist, 12 and walking or indoor cycling were the most common aerobic exercise modes. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Section 4 gathered information on the type of pre-exercise assessment and exercise tests used and how exercise training sessions were progressed. The design of previous Australian surveys 12 13 was considered to ensure novel information was collected. The survey primarily contained categorical variables with the option to include additional open-ended feedback on each question.…”
Section: Methodsmentioning
confidence: 99%